Revisiting the Nanoflow Cytometric Quantification of Extracellular Vesicles Under the Framework of ICH Q14 Guidelines - Ganghui Li; Qizhe Cai; Yanan Dong; Xiang Li; Xi Qin; Miaomiao Xue; Haifeng Song; Yi Wang (Journal of Extracellular Biology)
ABSTRACT Nanoflow cytometry (nanoFCM) is an increasingly important analytical procedure in every aspect of extracellular vesicle (EV) research, particularly in the development of EV‐based therapeutics. The main objective of this study was to evaluate and optimise the key determinant factors of nanoFCM in the quantification analysis of EVs to ensure its consistency and reliability in the development of EV therapeutic drugs, thereby serving as a potential quality control measure. Our investigation followed the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) Q14 guideline. We revisited the day‐to‐day practice of nanoFCM measurement for HEK293 cell‐derived and milk‐derived EVs (mEVs), focusing on optimising particle quantification and identifying risk factors. Initial evaluation of the procedure revealed a considerable lack of consistency and reliability, which was then subjected to extensive optimisation. The key outcomes of this study include: (1) an optimised analytic procedure incorporating Tween‐20, which significantly enhanced the precision and accuracy of the nanoFCM measurement and expanded the reportable range; (2) an analytical target profile (ATP) which provides a preliminary standard for future validation of nanoFCM procedures. Overall, this study serves as a foundation for future efforts towards the standardisation of analytical procedures for EV therapeutics.